MASLAHAH SEBAGAI TEORI PENETAPAN HUKUM: TELAAH ATAS KONSEP MASLAHAH IBNU QAYYIM AL-JAUZIYAH - Dainori Dainori (Postgraduate State Islamic Institute (IAIN) Metro, 2020)
In line with changes and the development of a society that is increasingly rapid, legal issues are increasingly complex. While every legal problem that develops in society is not all explicitly mentioned in the Koran, Hadith or ijma '. Whereas Islam as a religion must always be responsive and present to provide a solution to the growing legal problems. Mashlahah as one method of extracting the law is a suitable solution to address the legal problems that are developing at this time. However, so that the application of the mashlaah to explore and establish a law is not trapped in subjective matters and the interests of lust, then the use of these methods requires caution and understanding of the intact maqasid al-sharia and the use of strict mashlahah in accordance with the criteria that are Ulama 'Usul stipulated in order to achieve and find the law that is truly in accordance with the message of the law maker (shari'a).